Meningkatkan Aktivitas, Berpikir Kritis Dan Hasil Belajar Siswa Muatan IPA Menggunakan Kombinasi Model PBL, Make A Match Dan TGT Di SD - Shofia Zaujah Arsiani; Sakerani (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem in this research is the low level of activity, critical thinking skills and student learning outcomes in science learning hot material and its transfer. An effort to overcome this problem is to use a combination of Problem Based Learning (PBL), Make A Match and Teams Games Tournament (TGT) models in learning. The aim of this research is to analyze improvements in teacher activity, increase in student activity, increase in critical thinking skills and increase in learning outcomes. This research uses a qualitative approach with the type of Classroom Action Research (PTK), which consists of 2 cycles with 2 meetings each, which goes through the stages of planning, action implementation, observation and finally reflection. The research was conducted at 4 meetings, the subjects of this research were 18 grade 5 students at SDN Antasan Besar 1 Banjarmasin. Data from qualitative analysis, teacher activities, student activities, critical thinking skills and quantitatively, namely, learning outcomes. The data was analyzed using descriptive techniques and depicted in the form of tables and graphs, then interpreted using criteria for each indicator of success and the achievement of student learning completeness individually and classically. The results of the research showed that teacher activity at meeting 1 got a score of 28, meeting 2 got a score of 33, meeting 3 got a score of 34 and meeting 4 increased to get a score of 36. Student activity at meeting 1 got a percentage of 36%, meeting 2 got a percentage of 44%, at meeting 3 got a percentage of 72%, meeting 4 got a percentage of 94%. Then students' critical thinking skills at meeting 1 got a percentage of 11%, at meeting 2 got a percentage of 55%, at meeting 3 got a percentage of 77% and at meeting 4 got a percentage of 94%. Completeness of student learning outcomes increased from 22% to 94%. Based on the results of this research, it can be concluded that the combination of Problem Based Learning (PBL), Make A Match and Teams Games Tournament (TGT) models can improve the quality of teacher activities, student activities, critical thinking skills and student learning outcomes. The suggestion for teachers, students, school principals and other researchers is that this research can be used as a reference in using learning models that can improve the quality of teacher activities, student activities, critical thinking skills and student learning outcomes.